Analysis of the main requirements to the ethical behavior of civil servants in Ukraine: legal aspects - Sorokina, N. G. (Aspekty publichnoho upravlinni͡a, 2017)
Legal regulations that define the basic requirements to the ethical behavior of public servants in Ukraine have been analyzed in the article. It has been noted that the only recognition of the importance of professional ethics is not enough. One of the most effective measures of the public service authority’s improvement in society,  corruption combating and improvement of the governance culture is the legal regulation on the professional ethics of public service. It has been determined that the ethical principles of public service in Ukraine are noted in many Ukrainian legal acts, thus, the considerable attention in the paper was given to the study of the Laws of Ukraine “On State Service”, “On Corruption Prevention”, the Resolution of the Cabinet of Ministers of Ukraine “On approval of rules of the ethical behavior of public officials” and the Order of the National agency of Ukraine on civil service “On approval of the General rules of ethical behavior of civil servants and local government officials”. During analysis it has been determined that it is almost impossible to make a comprehensive list of rules of behavior of civil servants at the level of legal documents. So, the best guarantee of preventing power abuse, corruption and other service and ethical violation is personal dignity and high moral standing of employee and, above all, the professional honor and duty.